Burgers equation in the adhesion model. Issue 2 (22nd January 2022) - Gliklikh, Yuri; Shamarova, Evelina
Abstract : We prove the existence and uniqueness of a classical solution to a multidimensional non-potential stochastic Burgers equation with Hölder continuous initial data. Our motivation is the adhesion model in the theory of formation of the large-scale structure of the universe. Importantly, we drop the assumption on the potentiality of the velocity flow that has been questioned in physics literature.